The identities of Pulvinaria camelicola Signoret 1873, stat. nov., and the related species, Pulvinaria floccifera (Westwood 1870) (Hemiptera: Coccidae) in Japan - Tanaka, Hirotaka; Kamitani, Satoshi (Zootaxa, 2022)
The soft scale, Pulvinaria floccifera (Westwood 1870) (Hemiptera: Coccidae) is a well-known agricultural and horticultural plant pest; however, there is some confusion surrounding its true taxonomic identity. The type specimens of P. floccifera differ morphologically from specimens described under this name in several recent studies. This confusion has arisen because the original description is too brief, and subsequent redescriptions were based on non-conspecific material. This taxonomically problematic situation has led to further confusion regarding the identity of P. floccifera. Herein, the oldest junior synonym of P. floccifera, i.e., Pulvinaria camelicola Signoret 1873 stat. rev., is revived to confer taxonomic stability to P. floccifera. The revived name, P. camelicola, is applied to a distinct species hitherto misidentified as P. floccifera. Morphological details of the adult female of P. camelicola stat. rev. are updated; and the adult female of P. floccifera is redescribed, based on specimens collected in Japan and some type specimens. A lectotype of P. floccifera are designated to stabilise the species identity. A key to the species of Pulvinaria found in Japan, and a table of diagnostic morphological character states of P. floccifera, P. camelicola stat. rev. and the type species of the genus, P. vitis (Linnaeus 1758), are provided to facilitate further taxonomic revision of the genus in the future.